Rice No Pollen 1 (NP1) is required for anther cuticle formation and pollen exine patterning. (1st June 2017) - Liu, Ze; Lin, Sen; Shi, Jianxin; Yu, Jing; Zhu, Lu; Yang, Xiujuan; Zhang, Dabing; Liang, Wanqi
Summary: Angiosperm male reproductive organs (anthers and pollen grains) have complex and interesting morphological features, but mechanisms that underlie their patterning are poorly understood. Here we report the isolation and characterization of a male sterile mutant of No Pollen 1 ( NP1 ) in rice ( Oryza sativa ). The np1‐4 mutant exhibited smaller anthers with a smooth cuticle surface, abnormal Ubisch bodies, and aborted pollen grains covered with irregular exine. Wild‐type exine has two continuous layers; but np1‐4 exine showed a discontinuous structure with large granules of varying size. Chemical analysis revealed reduction in most of the cutin monomers in np1‐4 anthers, and less cuticular wax. Map‐based cloning suggested that NP1 encodes a putative glucose‐methanol‐choline oxidoreductase; and expression analyses found NP1 preferentially expressed in the tapetal layer from stage 8 to stage 10 of anther development. Additionally, the expression of several genes involved in biosynthesis and in the transport of lipid monomers of sporopollenin and cutin was decreased in np1‐4 mutant anthers. Taken together, these observations suggest that NP1 is required for anther cuticle formation, and for patterning of Ubisch bodies and the exine. We propose that products of NP1 are likely important metabolites in the development of Ubisch bodies and pollen exine, necessary for polymerization, assembly, or both. Significance Statement: The surface morphology of pollen is very diverse across plant taxa. How this pattern of morphology generates has been an open question for a long time. Here we revealed that NP1, encoding a GMC oxidoreductase, plays essential roles in pollen exine patterning and anther cuticle formation. We speculated that NP1 may participate in cross‐linking sporopollenin monomers during pollen wall formation.